Genome-wide identification and expression analysis of the HD2 protein family and its response to drought and salt stress in Gossypium species - Bano, Nasreen; Fakhrah, Shafquat; Lone, Rayees Ahmad; Mohanty, Chandra Sekhar; Bag, Sumit Kumar (Frontiers in Plant Science, 2023)
Histone deacetylase 2 (HD2) proteins play an important role in the regulation of gene expression. This helps with the growth and development of plants and also plays a crucial role in responses to biotic and abiotic stress es. HD2s comprise a C2H2-type Zn2+ finger at their C-terminal and an HD2 label, deacetylation and phosphorylation sites, and NLS motifs at their N-terminal. In this study, a total of 27 HD2 members were identified, using Hidden Markov model profiles, in two diploid cotton genomes (Gossypium raimondii and Gossypium arboretum) and two tetraploid cotton genomes (Gossypium hirsutum and Gossypium barbadense). These cotton HD2 members were classified into 10 major phylogenetic groups (I-X), of which group III was found to be the largest with 13 cotton HD2 members. An evolutionary investigation showed that the expansion of HD2 members primarily occurred as a result of segmental duplication in paralogous gene pairs. Further qRT-PCR validation of nine putative genes using RNA-Seq data suggested that GhHDT3D.2 exhibits significantly higher levels of expression at 12h, 24h, 48h, and 72h of exposure to both drought and salt stress conditions compared to a control measure at 0h. Furthermore, gene ontology, pathways, and co-expression network study of GhHDT3D.2 gene affirmed their significance in drought and salt stress responses.